2007
DOI: 10.1167/iovs.06-0950
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Retinal Nerve Fiber Layer Thickness after Acute Primary Angle Closure Measured with Optical Coherence Tomography

Abstract: This study demonstrated an initial increase in diffuse RNFL thickness after a single APAC episode, followed by a subsequent decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
(24 reference statements)
2
33
1
2
Order By: Relevance
“…The increase in RNFL thickness was possibly a response to the elevated IOP during surgery, similar to the IOP increase that occurs during an acute angle-closure glaucoma attack. 21,22 However, it may have also been the result of a change in the signal-tonoise ratio on OCT, as suggested by El-Ashry et al 24 Because there was no difference in the change in RNFL thickness between the 2 groups in our study, it appears as though the use of gas-forced infusion in phacoemulsification does not cause additional ganglion cell damage. However, it may be advisable to practice caution when considering its use in patients with advanced glaucomatous optic atrophy.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The increase in RNFL thickness was possibly a response to the elevated IOP during surgery, similar to the IOP increase that occurs during an acute angle-closure glaucoma attack. 21,22 However, it may have also been the result of a change in the signal-tonoise ratio on OCT, as suggested by El-Ashry et al 24 Because there was no difference in the change in RNFL thickness between the 2 groups in our study, it appears as though the use of gas-forced infusion in phacoemulsification does not cause additional ganglion cell damage. However, it may be advisable to practice caution when considering its use in patients with advanced glaucomatous optic atrophy.…”
Section: Discussionsupporting
confidence: 49%
“…Significant changes in RNFL thickness after episodes of acute congestive glaucoma 21,22 and laser in situ keratomileusis 23 have been documented by OCT. We found a gradual increase in the mean, superior, and inferior RNFL thicknesses without return to baseline levels 90 days after surgery, and the increase was similar in both groups. The increase in RNFL thickness was possibly a response to the elevated IOP during surgery, similar to the IOP increase that occurs during an acute angle-closure glaucoma attack.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been used to show axonal loss due to acute optic neuritis in multiple sclerosis [35]. Despite optic disc edema from optic neuropathy, RNF layer thickness may also be affected by retinal vein occlusion, anterior ischemic optic neuropathy, severe hypertensive retinopathy, or pseudopapilledema in congenitally crowded optic discs, or associated with optic disc drusen or even acute primary angle closure [36,37] and various other conditions. Real RNF layer defects may be masked during the edematous stage of the underlying disease, and the interval between edematous stage and measurement will influence the assessment of the RNF layer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that measured the changes in peripapillary RNFL thickness found that the changes occurred because of a sudden increase of IOP (>40 mmHg in less than 48 hours). 11,12 Eyes with IOP increased of more than 40 mmHg, had thinner peripapillary RNFL and these thinning also occured continuously until six months follow-up. In patients who never had sudden increase of IOP, the peripapillary thinning did not occur.…”
Section: Discussionmentioning
confidence: 93%
“…7,9,10 Several studies had been conducted on how the increasing IOP, either acutely or chronically, can damage the peripapillary nerve fibers on glaucoma and nonglaucoma patients. 6,11,12 The studies about the influence of phacoemulsification on the macula and peripapillary RNFL thickness have been done in non-glaucoma patients, but not in the glaucoma patients.…”
mentioning
confidence: 99%